Discontiguous recurrences of IDH-wildtype glioblastoma share a common origin with the initial tumor and are frequently hypermutated - Malcolm F. McDonald; Sricharan Gopakumar; Tareq A. Juratli; Ilker Y. Eyüpoglu; Ganesh Rao; Jacob J. Mandel; Ali Jalali (Acta Neuropathologica Communications)
Abstract Glioblastoma is the deadliest primary brain tumor, largely due to inevitable recurrence of the disease after treatment. While most recurrences are local, patients rarely present with a new discontiguous focus of glioblastoma. Little is currently known about the genetic profile of discontiguous recurrences. In our institutional database, we identified 22 patients with targeted exome sequencing of pairs of initial and recurrent IDH-wildtype glioblastoma. Recurrences were classified as contiguous or discontiguous based on the presence or absence of T2 FLAIR signal connection to the initial site of disease on MRI. Exome analysis revealed shared driver and passenger mutations between discontiguous recurrences and initial tumors, supporting a common origin. Discontiguous recurrences were more likely to be hypermutated compared to contiguous recurrences (p = 0.038). Analysis of 2 glioblastoma cases with discontiguous recurrence at a collaborating institution also exhibited hypermutation. In conclusion, discontiguous glioblastoma recurrences share a common origin with the initial tumor and are more likely to be hypermutated than contiguous recurrences.